Project Based Learning in Creating Creative And Productive Learning at 1st Class of SDN 3 Menggala Pemenang, Academic Year 2024/2025 - Sartika, Amelia; Sumiadi, Raden; Hadi, Rusman (International Journal of Education, Information Technology, and Others, 2025)
This research aims to describe the facts in the field regarding project-based learning in creating creative and productive learning in 1st class SDN 3 Menggala. The research has been conducted using several methods, namely observation, interview and documentation methods. The data analysis was carried out with several techniques, namely condensation, presentation and drawing conclusions so as to obtain valid data. To test the validity of the data obtained, researchers conducted several triangulation techniques, namely triangulation including triangulation of sources, time and triangulation of techniques. Then after conducting several research techniques the research found that the implementation of project learning in 1st class SDN 3 Menggala can create creative and productive learning which is implemented in learning Mathematics, Indonesian Language and SBDP. The learning is in the form of project learning to make picture number cards/tickets.